Afecções colônicas detectadas à colonoscopia em adultos sem sintomasdigestórios - Hermes Miranda de Oliveira (2010)
The incidence of colorectal cancer has been progressively increased in the recent years, with an important impact on health system. The purpose of testing for this disease is to detect individuals who require to undergo specific studies in order to treat colonic disturbances in their asymptomatic stages. Objective: To evaluate the use of colonoscopy inthe detection of pathologic conditions of the colonic mucosa in adults without abdominal and digestive symptoms or signs. Method: Fifty asymptomatic consecutive subjects who had undergone a colonoscopy were prospectively studied. Sex, age, body mass index, diet,positive family history for colorectal cancer, alcoholism and nicotine addiction were taken into account. The colonoscopic findings were related to the time spent on the exam and their complications. Individuals with abdominal and digestive signs and symptoms were notincluded. Presence of polyps, diverticula and neoplasms were investigated. Results: 70% of the subjects were women and 30% men. 42% of them referred family history of colorectal cancer. Other colonic findings were 12% hyperplasic polyps, 16% adenomas and 2% cancer ofsigmoid. Colonic polyposis was found in 4% of patients. Smoking was the only factor statistically associated with the presence of polyps (p<0, 02). Conclusion: Many diseases may be found in asymptomatic patients in ages above the fifty years old, mainly benign and malignant neoplasm.